Challenges and Advances in Aerosol Jet Printing of Regenerated Silk Fibroin Solutions. Issue 12 (27th April 2020) - Xiao, Yuhan; Kalaitzidou, Kyriaki; Yao, Donggang; Yeo, Woon‐Hong; Harris, Tequila A. L.
Abstract: Silk fibroin materials are manufactured using printing and coating techniques at resolutions 1–2 µm. However, current processes are unstable, of low printability and versatility, and of limited feature size, and often require use of additives to process, which can impact material functionality and performance. Although there exist well established material synthesis and formulation approaches for making processable solutions from silkworm cocoons, these approaches do not translate to the emerging fabrication processes, such as aerosol jet printing (AJP). Here, a new approach is introduced to formulate silk‐worm solutions for AJP and subsequently analyze the processing limits, due to defects such as overspray, pooling, and cloudiness. It is found that the degumming step is critical and can lead to defects such as gelling and pooling. Furthermore, it is found that there exists a narrow processing window (sheath rate as a function of ink rate) for AJP formulations without defects. As with other materials (such as metal inks), overspray is an issue during the fabrication process; however, it is minimized within the processing window. This work stands to open a pathway for manufacturing new and emerging biodegradable materials suitable for pharmaceuticals, food packaging, and electronics, among others. Abstract : Aerosol jet printing of regenerated silk fibroin solution is conducted. A printable solution is formulated that allows for aerosolizing and fabricating a variety for patterns, such as lines, circles, and letters. A process window that bounds the optimal region for printing this solution is presented, with special consideration for defects such as overspray, pooling, discontinuities, and poor focusing.